Hubungan Kecerdasan Emosional dan Sikap Terhadap Pelajaran Matematika Dengan Hasil Belajar Matematika Siswa SMA Jakarta Timur - Meitina Ventini; Hartati Hartati; Moch Sukardjo (JTP - Jurnal Teknologi Pendidikan, 2018)
The purpose of this study is to identify the magnitude of the relationship between variables of emotional intelligence, and students' attitudes towardmathematics learning outcomes. Using correlational research methods, both partial and multiple research respondents are class X high school students in EastJakarta as many as 150 students from 7 public and private schools selected by multistage random sampling. Data were collected in the form of primary datausing questionnaires, and mathematical tests that were tested for validity and reliability. The results that (1) emotional intelligence variables have a positive andsignificant relationship to mathematics learning outcomes, (2) student attitudes are positively and significantly related to mathematics learning outcomes, and (3)emotional intelligence and students' attitudes simultaneously related positive and significant towards the learning outcomes of mathematics.